Inland waterway ports selection and evaluation using stochastic analytical hierarchy process. Issue 3 (3rd July 2021) - Nur, Farjana; Marufuzzaman, Mohammad; Puryear, Stephen M.; Wall, Emily S.; Burch, Reuben
ABSTRACT: Inland waterway ports are an integral part of a country's transportation system and the overall economy it supports. Though these ports support and contribute to a country's import-export business and transportation economy, little attention is paid, primarily on the characterisation of these inland waterway ports. In this paper, we develop a systematic, multi-criteria, multi-personnel decision making approach, referred to as stochastic Analytical Hierarchy Process (AHP), that can be used to characterise inland waterway ports and to identify the factors that contribute most towards a port's performance and overall utilisation. This robust method can successfully handle judgment errors, biases, and inconsistencies, while reducing the uncertainty associated with decision-making. We use the state of Mississippi's inland waterways system as a testbed to visualise and validate the modelling results. Results indicate that the Mississippi River ports demonstrate less capability over the ports located along the Tennessee-Tombigbee waterway, based on the criteria used as a part of this study. A number of sensitivity analyses were performed, including additional investments, augmenting dredging capabilities, and introducing new businesses, to reveal managerial insights about the selection of inland waterway ports in Mississippi.